Sustained Effects of School-Based Obesity Education on Knowledge and Healthy Lifestyle Behaviors among Junior High School Students - Astin, Nur; Amalia, Alfiyyah; Sadarang, Rimawati Aulia Insani (Unihealth Community Research, 2026)
Obesity among adolescents is an increasing public health problem that contributes to the risk of various non-communicable diseases. Schools provide a strategic setting for health promotion to improve students' knowledge and encourage healthy lifestyles. This community service aimed to evaluate the effectiveness of an obesity education program by assessing students' knowledge six months after the intervention. The program involved 51 students of SMP Negeri 2 Parangloe selected through total sampling. A quantitative evaluative approach with a one-group pretest-posttest and follow-up evaluation design was applied. Data were collected using knowledge and behavioral questionnaires and analyzed using univariate analysis and the Friedman test. The results showed a significant improvement in students' knowledge (p=0.000), with the median score increasing from 3 at pre-test to 6 at post-test I and reaching 7 at the six-month follow-up. Furthermore, 75.0% of students reported engaging in regular physical activity, while 80.4% reduced their consumption of high-fat and high-sugar foods. These findings indicate that school-based obesity education is effective in improving and maintaining students' knowledge while encouraging healthier lifestyle behaviors for obesity prevention